Diversity is beneficial for a research group: One more quantitative argument - Suriya K. (World Academic Union, 2015)
© 2015 World Academic Press, UK. All rights reserved. In this paper, we propose a natural model describing competition between two research groups of the same average research strength. The analysis of this model enables us to conclude that a more diverse group has an advantage: namely, the more diverse the group, the higher the average quality of its publications.